Analysis of music teacher training programs: Structure of curriculum design in the field of music - ÖZGÜL, İlhan (Kastamonu Egitim Dergisi, 2021)
In this research, 2007 music teacher training program prepared by the Council Higher Education in Turkey and Education Faculty music teacher training program changed under adaptation, quality and accreditation to Bologna process in the field of 2018 European higher education were analysed. In this study characterised as a “field study” regarding the environment it was carried out, “descriptive” in terms of method and specifically “document analysis”, it was investigated to what extent music teacher training curriculum designs complied with program development principles, and relationships regarding courses defined within the scope of the program and the goals of the subject areas of music education. It has been found out that there were not sufficient number of members in the curriculum development committee based on “certain criteria” when amended Music Teacher Program Design was created, and there are contradictions between the scope of the curriculum and definition of courses, and there are significant number of theoretical courses in the curriculum. When examining the goals of courses specified related to the Music Teacher Field, allowing teachers to have in-depth understanding and knowledge on their field, in the four-year program, it was determined that the indicators related to “repeatability”, “permanence” and “progressivity” were very low/poor/insufficient. To conclude, suggestions were made related to the studies on reorganisation, update and amendment of the music teacher training curriculum (2018).
Keywords: 4. Education